Development and Validation of a Community Assessment Survey for Diverse Rural Family Caregivers of People With Alzheimer Disease and Related Dementias. Issue 3 (July 2021) - McCarthy, Michael J.; Lee-Regalado Hustead, Morgan; Bacon, Rachel; Garcia, Y. Evie; Dunn, Dorothy J.; Williamson, Heather J.; Baldwin, Julie
Abstract : Many individuals with Alzheimer disease and related dementias receive care from family members and friends. Rurality adds increased complexity to care, especially for diverse caregivers. This study details the development and content validation process for a community assessment survey for rural white, Latinx, and American Indian/Alaska Native Alzheimer disease and related dementias caregivers. Foundational survey items were based upon instruments validated with diverse rural caregivers. A modified Delphi process (2 rounds) was used to refine items. The process concluded when 75%+ of experts agreed that the survey was (1) inclusive of different cultural groups; (2) respectful of cultural values and norms; (3) comprehensive with respect to needs, assets, and resources, and (4) relevant to the experiences of diverse rural caregivers. Round 1 of the process (N = 9 panelists) resulted in the elimination of 2 survey sections, a greater focus on issues including transportation and roles of extended family members, and the inclusion of open-ended questions. Round 2 (N = 6 panelists) resulted in further improvements, particularly to the sections about cultural customs, beliefs, and traditions and interactions with health care and other providers. Benefits of the process included raising awareness about rural caregiving issues and maximizing data quality. Challenges included honoring the diversity of respondents' opinions and balancing research rigor with community utility. This community assessment survey may help researchers better understand the needs and culturally–based strengths of diverse rural family caregivers.